2010
DOI: 10.1021/bi101159s
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Expression, in Vitro Refolding, and Biophysical Characterization of the Human Glucagon-like Peptide-1 Receptor

Abstract: Activation of the glucagon-like peptide-1 receptor (GLP-1R) upon ligand binding leads to the release of insulin from pancreatic cells. This strictly glucose-dependent process renders the receptor and its ligands useful in the treatment of type II diabetes mellitus. To enable a biophysical characterization in vitro, we expressed the human full-length GLP-1R in the cytosol of Escherichia coli as inclusion bodies. After purification, refolding of the SDS-solubilized receptor was achieved by the exchange of SDS ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 43 publications
1
26
0
2
Order By: Relevance
“…reported the E . coli recombinant expression and in vitro refolding of functional hGLP1R, where K D value was unmeasurable for GLP-1 and determined to be ~180 nM for Ex-4 using fluorescence quenching and surface plasmon resonance methods [56], which is comparable to our results. On the other hand, a lower affinity can also be caused by (1) fluorescent labeling of the peptide ligands, (2) the non-native lipid environment and (3) absence of native receptor-affiliated proteins.…”
Section: Resultssupporting
confidence: 88%
“…reported the E . coli recombinant expression and in vitro refolding of functional hGLP1R, where K D value was unmeasurable for GLP-1 and determined to be ~180 nM for Ex-4 using fluorescence quenching and surface plasmon resonance methods [56], which is comparable to our results. On the other hand, a lower affinity can also be caused by (1) fluorescent labeling of the peptide ligands, (2) the non-native lipid environment and (3) absence of native receptor-affiliated proteins.…”
Section: Resultssupporting
confidence: 88%
“…Coding fragments for truncated PABPN1 variants were amplified from this vector and ligated into pET SUMOadapt (29). Recombinant protein production was performed by fermentation in complex medium in a 10-liter bioreactor (BIOSTAT C-DCU; Sartorius Stedim) as described previously (30) with the following modifications: at A 600 ϭ 40 -50, protein expression was induced with 1 mM isopropyl 1-thio-␤-D-galactopyranoside. The cultivation temperature was reduced to 30°C to prevent inclusion body formation.…”
Section: Methodsmentioning
confidence: 99%
“…The receptor belongs to family B GPCRs. To date, there have been a small number of successful cases of purifying family B GPCRs, which include pituitary adenylate cyclase-activating peptide receptor purified from bovine brain 29 and insect cells 30 , PTH1R purified from COS-7 cells 33 , HEK293S cells 11 and E. coli 27 , glucagon-like peptide 1 receptor purified from both E. coli 42 and insect cells 49 , and two other receptors, corticotrophin-releasing factor receptors 1 and 2β, obtained using cell-free expression methods 18 . In this study, we choose PTH1R as our target receptor, because it has been shown to be stable in detergents.…”
mentioning
confidence: 99%